1995
DOI: 10.1029/95jb02158
|View full text |Cite
|
Sign up to set email alerts
|

Earthquake focal mechanisms, deformation state, and seismotectonics of the Pamir‐Tien Shan region, Central Asia

Abstract: This paper presents a review of the seismotectonics of the Pamir‐Tien Shan collision zone in the Garm region, Tajikistan, based on geological structure, seismicity, and focal mechanism solutions. The region is dominated by horizontal compression, manifested by imbricate, low‐angle thrust faults that separate the upper crust into a series of tectonic sheets. These thrust systems verge northward from the Tajik Depression toward the southern Tien Shan and southward toward the northern Pamir. The pattern of seismi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 35 publications
1
30
0
Order By: Relevance
“…Several major earthquakes have occurred since the end of the 19 th century and thousands of smaller seismic events have been recorded (Lukk et al 1995). The major earthquake of the year 1887 (M s = 7.3) affected the large town Almaty (called Vernyi at that time) situated at the : Identification and monitoring of potentially dangerous glacial lakes in the northern Tien Shan.…”
Section: Figure 1 Around Herementioning
confidence: 99%
“…Several major earthquakes have occurred since the end of the 19 th century and thousands of smaller seismic events have been recorded (Lukk et al 1995). The major earthquake of the year 1887 (M s = 7.3) affected the large town Almaty (called Vernyi at that time) situated at the : Identification and monitoring of potentially dangerous glacial lakes in the northern Tien Shan.…”
Section: Figure 1 Around Herementioning
confidence: 99%
“…This surface-wave CMT methodology, which yields compatible and very similar results as in standard CMT, allows study of the complex processes of stress transfer to different fault segments that marked the unusual time evolution of the sequence (Arvidsson and Ekström 1998;Ekström et al 1998;Morelli et al 2000). Several workers (Menke and Jacob 1976;Armbruster et al 1978;Chatelain et al 1980;Seeber et al 1981;Ni and Ibenbrahim 1991;Fan et al 1994;Mellors et al 1995;Lukk et al 1995;Zhu et al 1997;Searle et al 2001;Khan 2003) have studied the seismicity and the geological processes of the northwestern part of the Indian plate, and have suggested that the seismicity in this region is apparently caused by the mutual interaction between the Kohistan Arc and the Indian plate (Fig. 1).…”
Section: Study Of Seismicitymentioning
confidence: 80%
“…Due to the northward indenting of the Pamir block into the Eurasian Plate (Lukk, et al, 1995;Neil, Houseman, 1997), the Tianshan Mountain from north and the Kunlun Mountain from south meet each other, squeezing the Tarim block and pressing its northwestern corner bending downward. To the north of the Jiashi earthquake region the Tianshan overthrust southward, overlying on the Tarim block and bending it downward.…”
Section: Discussionmentioning
confidence: 99%